Impacts of Revising Criminal Wrongful Convictions on Judicial Credibility in China: A Cocktail Party Effect Analysis - Said, Muhamad Helmi Md; Li, Yaoyao; Hassan, Muhamad Sayuti; Liu, Jingyu; Tinuk Dwi Cahyani (Journal of Law and Legal Reform, 2025)
In the Disruption Era, the revision of criminal wrongful convictions is vital to the protection of human rights. Moreover, it has a wide and profound impact on judicial credibility with complex mechanisms for shaping such impact. This commitment to rectify errors and uphold justice through criminal revision, while commendable, is overshadowed by a prevailing public perception that attributes such revisions to systemic deficiencies such as corruption, misuse of authority, and biased judicial decisions. This study delves into the intricate landscape of rectifying wrongful convictions by introducing the nuanced perspective of the Cocktail Party Effect (CPE), a sophisticated acoustic theory. The CPE’s impact unfolds in three distinct stages—aptly termed "Screen-Mask-Polarize"—as the public navigates through the revision process. At its core, this study elucidates how signals emanate from wrongful conviction revisions to undergo automatic screening, influenced by the public’s subjective preferences, thereby establishing a biased negative cognitive context. This cognitive bias, in turn, possesses the potential to erode public trust in the legal system and diminish confidence in the judiciary. Consequently, this comprehensive research offers insightful recommendations for judicial organs, the news media, and the public, complemented by two instrumental measures: the implementation of a state compensation system and the establishment of an accountability framework for wrongful convictions. The overarching goal of this study is to empower the public with the tools needed for a more objective and logical analysis of wrongful conviction revisions, fostering a nuanced understanding and trust in the criminal justice system.